Gastrointestinal Emergencies in the ICU. Issue 1 (January 2023) - Rao, Sheldon; Baltaji, Stephanie; Crow, Kyle; DiSilvio, Briana; Cheema, Tariq
Abstract : Gastrointestinal (GI) emergencies and disorders are among the most common reasons to be admitted to an intensive care unit (ICU). In addition, critically ill patients admitted to the ICU for non–GI-related diseases are frequently at risk of developing GI complications during their hospitalization. This article details the epidemiology/etiology, clinical presentation, diagnostic assessment, and management of the following GI emergencies: upper and lower GI bleed, acute pancreatitis, and ascending cholangitis.